DEMOCRACY AND THE FIGHT AGAINST LEADERSHIP CORRUPTION IN SUB-SAHARAN AFRICA: IMPLICATION FOR CONTINENTAL DEVELOPMENT - TAIWO FRANCIS AYOMOBA (International Studies Journal)
This paper examines democracy and the fight against leadership corruption in relation to Africa and its implication on development and security issues using a qualitative data gathering and analysis method. There is a particular Nigeria’s current governance system. Scholars frequently see corruption as a fundamental impediment to growth and development. Every society hates corruption and frequently holds the leaders accountable. Anti-corruption advocacy mechanisms exist all around the world to promote ethical leadership in government. For example, the African Union has adopted a set of continental anticorruption protocols to help member nations combat the rising tide of corruption and its ramifications for human security. It claims that the nature of African political leadership breeds a tendency for power abuse. We find that the political elite's entrenched vested interests have promoted corruption and abuse of power as instruments of governance, and have rendered the necessary statutory institutional oversight systems ineffectual. While society is gripped by governance crisis with all of its ramifications, the political elite lives in luxury. As a result, the study contends that if citizens continue to tolerate unethical behaviors by political leaders, the governance crisis caused by misuse of public resources by political leadership will worsen insecurity and underdevelopment in Nigeria, West Africa.